O impacto da motivação intrínseca e extrínseca na intenção de rotatividade dos docentes da Universidade Federal do Tocantins - Barbosa, Antonio Renato (Universidade Federal do Tocantins, 2020)
This article discusses the relationship between intrinsic and extrinsic motivation with the intention of teacher turnover at the Federal University of Tocantins, Araguaína campus, Cimba unit. The main objective was to assess whether intrinsic and extrinsic motivation has a statistically negative impact on the intention of teachers to leave the organization. This subject has been recurrent in the last years and several works have been presented on this topic, which shows the concern of the scholars with this subject, the personnel turnover, that can have negative impact on the performance of the organization if it is not diagnosed of form Correct. As for the nature of the research this work resorted to the descriptive, field research, in relation to the form is considered quantitative. The results obtained do not indicate evidence of statistically significant negative effect of the two types of motivation on the intention of teachers rotation, which shows the need to analyze the subject more deeply, either with the insertion of new elements related to motivation or increase in size Of the sample to be searched.